2019
DOI: 10.3390/md17060368
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Cell Protective Role of Histochrome under Oxidative Stress in Human Cardiac Progenitor Cells

Abstract: Cardiac progenitor cells (CPCs) are resident stem cells present in a small portion of ischemic hearts and function in repairing the damaged heart tissue. Intense oxidative stress impairs cell metabolism thereby decreasing cell viability. Protecting CPCs from undergoing cellular apoptosis during oxidative stress is crucial in optimizing CPC-based therapy. Histochrome (sodium salt of echinochrome A—a common sea urchin pigment) is an antioxidant drug that has been clinically used as a pharmacologic agent for isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Moreover, echinochrome was found to be a potential drug for enhancing cardiomyocyte differentiation in embryonic stem cells through direct binding to protein kinase C iota type (PKC-iota) and inhibition of its activity. 37,38) The protective effect of histochrome (echinochrome) pretreatment of human cardiac progenitor cells (hCPCs) against hydrogen peroxide (H 2 O 2 )-induced oxidative stress was investigated. It was found that histochrome-treated hCPCs showed significant protective effects against H 2 O 2 -induced cell death.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, echinochrome was found to be a potential drug for enhancing cardiomyocyte differentiation in embryonic stem cells through direct binding to protein kinase C iota type (PKC-iota) and inhibition of its activity. 37,38) The protective effect of histochrome (echinochrome) pretreatment of human cardiac progenitor cells (hCPCs) against hydrogen peroxide (H 2 O 2 )-induced oxidative stress was investigated. It was found that histochrome-treated hCPCs showed significant protective effects against H 2 O 2 -induced cell death.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…10) which contain phenylamino-phenylthio moieties as significant counterparts demonstrated major antibacterial activity against bacterial strains Staphylococcus aureus, Listeria monocytogenes, E. coli, P. aeruginosa, Salmonella bongori and Klebsiella pneumoniae. [57][58][59] Two naphthoquinone derivatives (38) and (39) (Fig. 10) had potential antimycobacterial activity against three Mycobacterium tuberculosis strains and did not exhibit cross-resistance with isoniazid and rifampicin; they could be promising scaffolds for the development of new therapeutic strategies against tuberculosis.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…Histochrome delayed the progression of cellular senescence in hCPCs. It was concluded that the use of histochrome as biosafe agent is promising as potential therapeutic strategy at application of patients-derived hCPCs to treat cardiovascular diseases [10].…”
Section: Ofmentioning
confidence: 99%
“…There are ongoing debates related to definitions of cell lineage in cardiac stem cells. Originally believed to have no capacity for self-renewal due to mature cardiomyocytes' exit from the cell cycle, the heart is now believed to be residence to several different populations of stem or progenitor cells, with the potential for cardiac repair [48]. These cells are speculated to originate from a single cardiac stem cell type, and the different populations to represent different physiological stages of the parent stem cell [49].…”
Section: Differentiation Of Cpcs Into Cmsmentioning
confidence: 99%